Sosialisasi Peran Penting Sinergitas Antara Sekolah dan Keluarga dalam Pengembangan Sosial Emosional Anak di TK Desa Popodu Kecamatan Bolaang Uki Kabupaten Bolaang Mongondow Selatan - Nunung Suryana Jamin; Icam Sutisna; Rapi Us. Djuko; Sri Wahyuningsi Laiya; Fitriah Suryani Jamin; Sulastya Ningsih; Risa Novila Satingi (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
This activity aims to socialize the importance of school and family synergy in children's social and emotional development. This activity uses a lecture method, namely by presenting socialization material followed by questions and answers between the presenter and participants. During childhood, children's emotional development is not yet stable, so it becomes a problem for children in socializing. For example, temper tantrums, anxiety, phobias, and aggression. In Kindergarten in Popodu village, Bolaang Uki district, these problems arise more often because the social environment is wider and more diverse than the family. To overcome these problems, school and family synergy is needed. The implementation of socialization begins with the presentation of the first resource person, then continues with the second resource person and ends with a question and answer session for participants and resource persons. This activity produces additional information for participants in the form of understanding and knowledge about the importance of collaboration between teachers and parents in developing children's social emotions. Forms of collaboration that can be carried out include: dialogue and meetings between teachers and parents, involving parents and teachers in efforts to support children's development both in the family and at school as well as reciprocal visits between teachers and parents at home and at school.